Inhibition of Panx1 reduces neuroinflammatory response and alleviates brain damage in septic mice - Lei, Yueyi (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Objective: This study mainly investigates whether Pannexin 1 protein (i.e. Panx1) plays a role in the progression of brain injury in sepsis mice and its potential mechanisms. Methods: A total of 45 clean grade adult male C57BL/6 healthy mice were selected and divided into three groups using a random number table method, namely the sham group, the cecal ligation perforation (CLP) group, and the CBX pretreatment plus cecal ligation perforation (CBX+CLP) group, with 15 mice in each group. Excluding the Sham group, the remaining two groups of study mice were used to prepare sepsis brain injury models using the CLP method. The CBX+CLP group was injected into the lateral ventricles of both sides of the mouse half an hour before the modeling process, with a total amount of 1 μL CBX, which was injected into the bilateral lateral ventricles of the other two groups of mice with the same dose of physiological saline solution. 24 hours after the completion of modeling, three groups of mice were evaluated for neurological behavior. Subsequently, all mice were euthanized. After the cardiac perfusion phase, brain tissue of the mice was taken to observe the pathological damage of the hippocampal tissue. The effective content of IL-1β and TNF‐α in the mouse’s hippocampal tissue was measured, and the expression of Panx1 protein, Caspase-1, NLRP3 protein, as well as NLRP3, Panx1, Caspase-1, TNF‐α, IL-1β were measured the mRNA of corresponds to its expression status. Results: Compared with Sham group mice, the neurobehavioral score of CLP group mice significantly decreased, and the pathological damage degree of hippocampal neurons in mice was significant. The expression levels of inflammatory factors IL-1β and TNF‐α were increased, and the corresponding expression levels of Panx1, NLRP3, Caspase-1 proteins and mRNA were increased. The mRNA expression levels of inflammatory factors IL-1β and TNF were also increased (P<0 05), compared to the CLP group mice, the CBX+CLP group mice showed an increase in neurobehavioral scores, a reduction in pathological damage to hippocampal tissue, a decrease in the expression of inflammatory factors IL-1β and TNF‐α, a decrease in the expression levels of NLRP3, Panx1, Caspase-1 proteins, and corresponding mRNA, and a corresponding decrease in the mRNA expression of the two inflammatory factors (P<0 05). Conclusion: Inhibiting Panx1 can reduce the degree of neural inflammatory response, thereby improving brain damage in sepsis mice, which may be related to the limited activation of NLRP3 inflammasomes.